Mixed methods investigation of the use of telephone triage within UK veterinary practices for horses with abdominal pain: A Participatory action research study - Lightfoot, Katie L.; Burford, John H.; England, Gary C. W.; Bowen, I. Mark; Freeman, Sarah L. (PLOS ONE, 2020)
Background Telephone triage is an integral part of modern patient care systems in human medicine, and a key component of veterinary practice care systems. There is currently no published research on telephone triage within the veterinary profession. Objective To investigate current approaches to telephone triage of horses with abdominal pain (colic) in veterinary practice and develop new resources to support decision-making. Study design Participatory action research using mixed-methods approach. Methods An online survey assessed current approaches to telephone triage of horses with colic in UK veterinary practices. Structured group and individual interviews were conducted with four equine client care (reception) teams on their experiences around telephone triage of colic. Evidence-based resources, including an information pack, decision flow chart and recording form, were developed and implemented within the practices. Participant feedback was obtained through interviews six months after implementation of the resources. Results There were 116 participants in the online survey. Management and client care staff (53/116) felt less confident giving owner advice (p<0.01) and recognising critical indicators (p = 0.03) compared to veterinary surgeons and nurses (63/116). Thirteen themes were identified in the survey relating to owner advice; exercise and owner safety were most frequently mentioned, but conflicting guidance was often given. Fourteen client care staff were interviewed. They were confident recognising colic during a telephone conversation with an owner and identified the most common signs of critical cases as sweating and recumbency. The new resources received positive feedback; the decision flow chart and information on critical indicators were identified as most useful. After resource implementation, there was an increase in confidence in recognising critical cases and giving owners advice. Main limitations Limited sample population. Conclusions This study described existing approaches to telephone triage, identified variations in advice given, and worked with client care teams to develop new resources to aid decision-making.